CORRELATIONS BETWEEN CONTEMPORARY METHODS IN THE DIAGNOSIS OF CHLAMYDIA TRACHOMATIS UROGENITAL INFECTIONS. - Ilko Bakardzhiev; George Pehlivanov; E. Kovachev (Peytchinski Publishing, 2011)
The subject of this study were 486 outpatients between the ages of 17 and 62, diagnosed with urethritis, epidydimitis, prostatitis, cervicitis, endocervicitis, pelvic inflammatory disease and sterility. The following tests were used to make the diagnosis of Chlamydia trachomatis: Enzyme Immunoassay (EIA), Enzyme-Linked Fluorescent Assay (ELFA), Polymerase Chain Reaction DNA amplification for Chlamydia Trachomatis, Neisseria Gonorrhoeae, Mycoplasma Genitalium and Ureaplasma Urealyiticum. Comparison PCR and EIA showed statistically significant difference between the positive results obtained by the two methods (p<0,001). Comparing PCR and ELFA on the other hand, did not show any statistically significant difference (p>0,1). EIA is a method that gives a higher percentage of nonspecific positive reactions, while the results obtained from ELFA are much closer to the ones obtained by PCR. According to contemporary evidence based medicine, the developmet of unified standard methods for diagnosis and evaluation is of vital importance, not only for the patient and the treating physician but also concerns for the healthcare system, the general public and the pharmaceutical companies as well.